2014
DOI: 10.1007/s10751-014-1095-7
|View full text |Cite
|
Sign up to set email alerts
|

Iron (III) sulfide particles produced by a polyol method

Abstract: Iron(III) sulfide Fe 2 S 3 particles were produced using a polyol method. Although pyrrhotite Fe 1−x S appeared together with Fe 2 S 3 , the relative yield of Fe 2 S 3 changed when the concentration of reagents in the oleylamine changed. Mössbauer spectra of the particles showed superparamagnetic doublets due to Fe 2 S 3 at 293 K, along with a hyperfine magnetic splitting of H = 24.7 T at 6 K. XRD patterns of the Fe 2 S 3 suggested a structure similar to that of greigite Fe 3 S 4 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…While the detailed assignment of the doublet species cannot be unambiguously made with only Mossbauer parameters due to the diversity of species that are present, the observed parameters are in the range expected for mononuclear Fe− nitrogen species commonly present in iron ORR catalysts such as low-spin and high-spin FeN 4 type sites, as well as previously proposed Fe 2 N 5 binuclear sites. 11,12,15,38 For the sextet species, Sext 1 has parameters consistent with a bulk Fe−sulfide species (such as pyrrhotite 40,41 ) while Sext 2 is attributed to a bulk Fe− carbide species, similar to the previous observation of bulk sulfide and carbide species in PANI−Fe−C. 11 The minor singlet species is consistent with superparamagnetic Fe nanoparticles as previously assigned.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…While the detailed assignment of the doublet species cannot be unambiguously made with only Mossbauer parameters due to the diversity of species that are present, the observed parameters are in the range expected for mononuclear Fe− nitrogen species commonly present in iron ORR catalysts such as low-spin and high-spin FeN 4 type sites, as well as previously proposed Fe 2 N 5 binuclear sites. 11,12,15,38 For the sextet species, Sext 1 has parameters consistent with a bulk Fe−sulfide species (such as pyrrhotite 40,41 ) while Sext 2 is attributed to a bulk Fe− carbide species, similar to the previous observation of bulk sulfide and carbide species in PANI−Fe−C. 11 The minor singlet species is consistent with superparamagnetic Fe nanoparticles as previously assigned.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…Mössbauer measurements revealed that surprisingly the sulfidation time has no significant impact on the amount of metallic iron remaining in the core‐shell particles (∼55% in 4 A – C ). The shell likely exhibits the Fe 2 S 2 and Fe 7 S 8 phases (as present in nanoflakes 2 and 3 ), and a further phase, which presumably can be attributed to the non‐stoichiometric iron sulfide Fe 1−X S (for details see ESI).…”
Section: Resultsmentioning
confidence: 99%
“…WAXS analyses of samples 5 A and 5 B confirm the presence of α‐iron, while Mössbauer studies strongly suggest the formation of a Fe 1−X S phase in the shell (ESI). Interestingly, the shell composition evolves with time: a relatively sulfur‐rich phase (Fe 2 S 3 ) was detected at the very beginning of the sulfidation process ( 5 B ) before disappearing at longer reaction time ( 5 A ). In the mean time, the amount of Fe(0) remains fairly constant (∼65%).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the gaseous stream containing H 2 S, O 2 , CH 4 , CO 2 , COS, CS 2 , SO 2 , H 2 , and N 2 (diluent) is performed with the mass spectrometer quadrupole (Hiden HPR-20). The CO measurement is not performed because the analysis is affected by interference due to N 2 having the same m/z ratio (28).…”
Section: Methodsmentioning
confidence: 99%